Evaluasi Kebijakan Pengelolaan Sampah Di Kabupaten Bangkalan - Ahmad, Intan Nurmalasari; M, Dr. Lukman Arif, (Institut Riset dan Pengembangan Indonesia, 2023)
The purpose of this research is to analyze and describe the evaluation of waste management policies at Buluh TPA in Bangkalan Regency. The Bangkalan Regency Government faces several obstacles in dealing with the waste problem, including: a) The considerable distance between the TPA and its source. b) Limited facilities and infrastructure. c) High operational costs for transportation. d) The leachate pond is not functional. e) Monitoring wells and surrounding vegetation near the TPA are not utilized. f) Communities taking advantage of the presence of the TPA. The evaluation of waste management policies in Bangkalan must be conducted periodically and comprehensively, involving various stakeholders. The evaluation outcomes will serve as the foundation for enhancing policies that are more effective and sustainable in waste management in Bangkalan Regency.